Sotn ureteroscope system with vacuum suctioning device for treating complicated steinstrasse: a case series - Zhang, Zhaolin; Xiao, Shuiqing; Zeng, Qingming; Liu, Linwei; Xie, Tianpeng; Wang, Xiaoning (Frontiers in Surgery, 2025)
ObjectivesTo evaluate the safety and efficacy of sotn ureteroscope system with vacuum suctioning device for treating complicated steinstrasse.Materials and methodsThe medical records of 22 patients with complicated steinstrasse who underwent ureteroscopic lithotripsy via sotn ureteroscope system with vacuum suctioning device from January 2020 to March 2023 were summarized retrospectively. Five patients had ipsilateral renal calculi. The 11.5/12.5 F sotn ureteral access sheath (sotn-UAS) was placed below the lowermost section of the steinstrasse assisted by a 7.5/9.8 F standard ureteroscope, and then a 4.0/6.0 F console ureteroscope with laser fiber replaced the standard ureteroscope and was used for pulverizing the steinstrasse. The vacuum suctioning device was connected to the sotn-UAS for suctioning fragments and dusts.ResultAll procedures were successfully completed. The steinstrasse was free in 22 patients according to kidney-ureter-bladder radiography one day postoperatively. No intraoperative complications were observed. A total of four patients experienced postoperative complications, including one patient who experienced fever and was treated with antipyretics, one patient who experienced hematuria and was cured with hemostatic agents, and two patients who experienced urinary tract infection and needed only antibiotics. Five patients with ipsilateral renal calculi were treated with medical expulsive therapy or retrograde intrarenal surgery after steinstrasse surgery, and four of these patients achieved stone free status at the 3-month follow-up.ConclusionThe Sotn ureteroscope system with vacuum suctioning device is a feasible and safe treatment for complicated steinstrasse and provides satisfactory clinical outcomes.